Religious Moderation in Addressing Gender, Human Rights, and Ecology Issues: A Study from the Perspective of Contemporary Islamic Studies - Ridwan, Mohammad; Andaryuni, Lilik (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
The family is the smallest social unit and serves as a fundamental foundation for shaping individual character and values within society. Ideally, family relationships should foster balanced and equitable interactions among members. However, various forms of gender inequality continue to persist in family life. These inequities are reflected in unequal role distribution, limited involvement of women in decision-making, disproportionate domestic workloads, and the occurrence of gender-based violence. This study aims to identify and analyze manifestations of gender inequality in family relations and to explore strategic efforts to promote equality. Using a descriptive qualitative approach and a literature study method, the research examines academic literature, legal documents, and previous studies through the lens of gender perspectives and family sociology. The findings reveal five major forms of gender inequality—marginalization, subordination, stereotyping, violence, and excessive workload—all of which have systemic impacts on the well-being of family members, particularly women and children. To address these issues, it is essential to deepen understanding of gender concepts, ensure fair distribution of household responsibilities, promote shared decision-making, and practice transparent financial management. Achieving gender equality within the family not only supports healthy emotional and social development of individuals but also contributes to building an inclusive, harmonious, and gender-just society.